2003
DOI: 10.1046/j.1432-1033.2003.03809.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated transglutaminase from Streptomyces mobaraensis is processed by a tripeptidyl aminopeptidase in the final step

Abstract: Transglutaminase (TGase) from Streptomyces mobaraensis is secreted as a precursor protein which is completely activated by the endoprotease TAMEP, a member of the M4 protease family [Zotzel, J., Keller, P. & Fuchsbauer, H.‐L. (2003) Eur. J. Biochem. 270, 3214–3222]. In contrast with the mature enzyme, TAMEP‐activated TGase exhibits an additional N‐terminal tetrapeptide (Phe‐Arg‐Ala‐Pro) suggesting truncation, at least, by a second protease. We have now isolated from the culture broth of submerged colonies a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 26 publications
(36 reference statements)
1
66
0
2
Order By: Relevance
“…For protein sequence analysis, tiny contaminations were removed by borate gel electrophoresis, as described elsewhere. [5][6][7] Sequence analysis was performed by Edman degradation (Procise 494 Protein Sequencer, Applied Biosystems, Weiterstadt, Germany).…”
Section: -7)mentioning
confidence: 99%
“…For protein sequence analysis, tiny contaminations were removed by borate gel electrophoresis, as described elsewhere. [5][6][7] Sequence analysis was performed by Edman degradation (Procise 494 Protein Sequencer, Applied Biosystems, Weiterstadt, Germany).…”
Section: -7)mentioning
confidence: 99%
“…Streptomyces transglutaminase is initially secreted as a pro-transglutaminase that could subsequently be activated by several exogenous proteases. Furthermore, Zotzel et al (2003) found that endogenous protease could also activ ate S. mobaerensis MTGase. According to Zhang et al (2009) differentiation, in which it is secreted and activated during the differentiation event.…”
Section: Mtgase Activity Of Streptomyces Thioluteus Tta 02 Sds 14 Culmentioning
confidence: 99%
“…The pro-peptide appears to be cleaved by a specific metalloprotease in the culture medium of S. mobaraensis. 50,51) Heterologous gene expression of microbial TGase has also been reported using Escherichia coli as the host, although difficulties were encountered in getting TGase secreted in an active form. 52) Recently, secretion of active TGase was reported by coexpression of a subtilisin-like protease in a Streptomyces or Corynebacterium expression system.…”
Section: Efficient Secretion Of Transglutaminasementioning
confidence: 99%